Real‐time measurement of electrode impedance during intracochlear electrode insertion123. (25th March 2013) - Tan, Chin‐Tuan; Svirsky, Mario; Anwar, Abbas; Kumar, Shaun; Caessens, Bernie; Carter, Paul; Treaba, Claudiu; Roland, J. Thomas
Abstract Objectives/Hypothesis: This pilot study details the use of a software tool that uses continuous impedance measurement during electrode insertion, with the eventual potential to assess and optimize electrode position and reduce insertional trauma. Study Design: Software development and experimental study with human cadaveric cochleae and two live surgeries. Methods: A prototype program to measure intracochlear electrode impedance and display it graphically in real time has been developed. The software was evaluated in human cadaveric temporal bones while simultaneously making real‐time fluoroscopic recordings and in two live surgeries during intracochlear electrode insertion. Results: Impedance changes were observed with various scalar positions, and values were consistent with those obtained using clinically available software. Using Contour Advance electrodes, impedance values increased after stylet removal, particularly when using the monopolar mode. Conclusions: Impedance values seem systematically affected by electrode position, with higher values being associated with proximity to the cochlear wall. The new software is capable of acquiring impedance measurements during electrode insertion, and these data may be useful to guide surgeons to achieve optimal and atraumatic electrode insertion, to guide robotic electrode insertion, and to provide insights about electrode position in the cochlea.